Competency analysis and educational strategies to meet the demand for a learning health system workforce - Sue S. Feldman; Ashleigh Allgood; Allyson G. Hall; Christy Harris Lemak; Eta S. Berner (Wiley, 2022)
Abstract Learning Health Systems (LHS) require a workforce with specific knowledge and skills to identify and address healthcare quality issues, develop solutions to address those issues, and sustain and spread improvements within and outside the organization. Educational programs are tasked with designing learning opportunities that can meet these organizational needs. This manuscript explores different mechanisms for addressing challenges to creating educational programs to prepare individuals who can work in and lead LHS. Strategies and recommendations for educational programs to support the LHS include the creation of a new program, collaborating across existing programs, and producing a set of instructional materials.